Validation of the Turkish Version of the Rapid Eye Movement Sleep Behavior Disorder Questionnaire - Yapan, Saadet; Comert, Itir Tari; Pelin, Zerrin; Aricak, Tolga (HINDAWI PUBLISHING CORP, 2016)
The aim of this study was to assess the validity and reliability of a Turkish version of the rapid eye movement sleep behavior disorder questionnaire (the RBDSQ-T) for identifying patients with rapid eye movement sleep behavior disorder (RBD) and to ensure that this tool can be applied in Turkish language. Three groups were enrolled to validate the RBDSQ-T: 78 healthy controls, 17 patients previously diagnosed with RBD, and 28 patients with obstructive sleep apnea syndrome (OSAS). Based on a cut-off score of five, the RBDSQ-T was able to discriminate RBD patients from healthy controls with sensitivity of 100% and specificity of 87%. Accordingly, 63% of patients were correctly diagnosed using the RBDSQ-T. Similarly, with a cut-off score of five, the RBDSQ-T was able to discriminate RBD from OSAS with sensitivity of 100% and specificity of 64%. Assessment of test-retest reliability and internal consistency reliability using Kuder-Richardson 20 analysis revealed a test-retest correlation coefficient of 0.95 and a Kuder-Richardson 20 value of 0.82. The findings demonstrate that the RBDSQ-T is a valid and reliable tool.
Keywords: SCREENING QUESTIONNAIRE; UTILITYX; INJURY